STUDENTS’ PERCEPTION TOWARD THE ENGLISH TEACHER’S TEACHING STYLE ON THE EIGHTH-GRADE STUDENTS AT SMP NEGERI 7 BAUBAU - Sanaria Maneba; Asti Wahyuni B; Vebby Chintya Vranciska (English Education Journal, 2023)
Problem statement that is answered in this research is what is the teaching style the English teacher use in teaching English at the eighth-grade students of SMP Negeri 7 Baubau. The objective of this research was to find out the teaching style the English teacher use in teaching English at the eighth-grade students of SMP Negeri 7 Baubau. The research used a quantitative approach with applying the descriptive method. The population of this research was the eighth-grade students of SMP Negeri 7 Baubau who registered in the school year of 2022/2023 in odd semester. In taking sample of the population, the researcher used cluster sampling technique by taking 60 students to be the sample of this research. Instrument that was used in this research will be a teacher style questionnaire. Technique of data analysis that was applied in this research is a descriptive statistics. Based on the finding of the research and the data analysis, it was found that the mean score of expert style was 2.9 which achieves high category, the mean score of formal authority style was 2.7 which achieves moderate category, the mean score of personal model style was 2.5 which achieves moderate category, the mean score of facilitator style was 2.9 which achieves high category, and the mean score of delegator style was 2.8 which achieves moderate category. From those results, it could be concluded that the most teaching styles used by the English teacher at grade eight at SMP Negeri 7 Baubau were the expert style and the facilitator style.